Appearance of Technical-Tactical Actions of Football Players with Different Role in the Game (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article describes the special exercises aimed at improving the technical and tactical actions of the players in the team and various roles and the technical and tactical actions of the players during the game.